Notes on Strobilanthes: The Sympagis group - Wood, J; Bennett, JR; Scotland, R (2003)
The 30 species that comprise the group of Strobilanthes species centred on the genus recognised by Bremekamp under the name Sympagis are discussed. It is shown that the defining character of the pollen is inconsistent and the characteristic globose, ribbed pollen intergrades with the ellipsoidal, ribbed pollen predominant in Strobilanthes, as well as with the less common globose, echinulate pollen. Other morphological characters are equally unsatisfactory in defining the group and lend no support to Bremekamp's division of Strobilanthes into numerous small genera. The 30 species are listed systematically together with taxonomic notes, geographical distributions and diagnostic features. Six new species are described (Strobilanthes asymmetrica, S. calcicola, S. kachinensis, S. pendula, S. rivularis, S. teraoi), one new name (S. bremekampiana) is proposed and three new combinations (S. affinis, S. renschiae and S. orthostachya) are made. Strobilanthes imbricata is lectotypified to clarify its disputed identity. Line drawings and pollen photographs illustrate many of the species and maps are provided to show the unusual distribution of certain species.